Adverse effects of systemic isotretinoin therapy: a study of 78 patients - Ahmed, Ijaz; Wahid, Zarnaz; Nasreen, Sarwat (Journal of Pakistan Association of Dermatologists, 2016)
Background Isotretinoin is an effective treatment for severe forms of acne refractory to other therapies, but it is a teratogen and can cause serious side effects. The side effects, in addition to the constitutional features are related to skin, mucosae, eyes, sexual organs, central nervous system, respiratory system and gastrointestinal tract. Deranged biochemical profile may also be seen in few patients. Objective The current study was aimed to determine the frequency of side effects of systemic isotretinoin therapy in patients treated for acne, thereby assessing its safety. Patients and methods During the calendar year 2004, all the acne patients attending the outpatient department of dermatology, Ziauddin Medical University, KDLB campus, Karachi, fulfilling the inclusion criteria, managed on systemic isotretinoin were enrolled. All were taking isotretinoin at a dose of 0.5mg/kg body weight daily. Baseline investigations were performed in all the patients i.e. liver function tests, lipid profile, complete blood picture and renal function tests. They were followed up for any side effects and clinical improvement. The baseline investigations were repeated monthly to see any biochemical and hematological derangements.Â Results 78 patients, 42 females (53.8%) and 36 males (46.2%), with ages ranging from 18 to 24 years, were enrolled. 72 patients (92.2%, p<0.001) developed side effects with a variable frequency of at least one feature in each of these subjects. The side effects, in addition to the constitutional features, observed were related to skin (87.2%), mucosae (10.3%), central nervous system (5.2%), eyes (3.8%), reproductive organs (2.6%), respiratory system (1.3%) and gastrointestinal tract (1.3%). Deranged biochemical profile was also a feature in few patients (6.3%). Conclusion The majority of the patients on systemic isotretinoin have side effects, the most common being cutaneous and mucosal but are trivial.Â Side effects pertaining to the other systems are less frequent.Â